2017
DOI: 10.1152/ajpgi.00394.2016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cav1.3 calcium channel in the human and mouse colon: posttranscriptional inhibition by IFNγ

Abstract: It has been hypothesized that apically expressed L-type Ca channel Ca1.3 (encoded by CACNA1D gene) contributes toward an alternative TRPV6-independent route of intestinal epithelial Ca absorption, especially during digestion when high luminal concentration of Ca and other nutrients limit TRPV6 contribution. We and others have implicated altered expression and activity of key mediators of intestinal and renal Ca (re)absorption as contributors to negative systemic Ca balance and bone loss in intestinal inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Therefore, these data do not exclude additional complementary mechanisms of IBD-associated bone loss that occur through nutritional deficits or altered osteoblast function, which have been highlighted in previous studies. 31 , 32 , 33 , 59 , 60 , 61 , 62 We did observe bone loss in colitis models that were not associated with significant weight loss, which is consistent with previous reports and may point to mechanisms that are independent of nutritional status. 33 Future studies should address the relative contributions of OCPs, nutritional status, and osteoblast function in contributing to bone loss during intestinal inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these data do not exclude additional complementary mechanisms of IBD-associated bone loss that occur through nutritional deficits or altered osteoblast function, which have been highlighted in previous studies. 31 , 32 , 33 , 59 , 60 , 61 , 62 We did observe bone loss in colitis models that were not associated with significant weight loss, which is consistent with previous reports and may point to mechanisms that are independent of nutritional status. 33 Future studies should address the relative contributions of OCPs, nutritional status, and osteoblast function in contributing to bone loss during intestinal inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…5 Our study found significantly lower concentrations of calcium in the CD patients compared with the control group, especially in patients in the active phase, with 60.8% of overall CD patients and 75.7% of those in the active phase being hypocalcaemia. In particular, the negative calcium balance behind hypocalcaemia has been found to be associated with a higher incidence of osteoporosis, together with fractures, in patients with CD, 17,18 thus affecting their long-term prognosis. Above all, a major cause of the negative calcium balance was insufficient supplementation of dietary calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Both intestinal subclinical inflammation and dys biosis may affect the absorption of calcium and other nutrients. Experiments on human cells and experimen tal models of IBD showed that interferongamma (IFNγ) can downregulate the expression in colon of Ltype calcium channels [19], and that inflammation may over all repress the expression of TRPV6, calbindin D9K and other calcium transporters in the duodenal epithelium [20], thus reducing the amount of absorbable calcium.…”
Section: Calcium Absorption and Homeostasis In Ankylosing Spondylitismentioning
confidence: 99%
“…Additionally, it has been estimated that onethird of IBD subjects have an inadequate calcium intake due to dietary habits [23]. Notably, supplementation with calcium and vitamin D may be insufficient to prevent osteo porosis in IBD patients, and this may be due to the downregulation of calcium transporters in inflamed gut mucosa as reported in preclinical studies [19,20].…”
Section: Calcium Absorption and Homeostasis In Ankylosing Spondylitismentioning
confidence: 99%